PENGARUH SISTEM INFORMASI PENGELOLAAN KEUANGAN DAERAH DAN BIMBINGAN TEKNIS KEUANGAN TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN LEBAK - Taufiqurrohman Taufiqurrohman; Ita Puspita (Sekolah Tinggi Ilmu Ekonomi La Tansa Mashiro, 2020)
This This study aims to analyze the effect of the Regional Financial Management Information System and Financial Technical Guidance on the Quality of the Lebak Regency Regional Government Financial Statements for the period 2012-2016. Because of an increase in opinion from the Financial Supervisory Agency from the previous year. This is an interesting phenomenon that occurs in Lebak Regency.The method of research conducted by the author is a quantitative method. Respondents in this study were all financial administration officials (PPK), expenditure treasurers, revenue treasurers and regional financial management information system operators in 30 regional organizations at the level of Agency / Service in Lebak Regency, amounting to 99 respondents. Data retrieval is done by using a sample non probability sampling in the form of purposive sampling. Data obtained 94 respondents from 99 questionnaires distributed. The data obtained were analyzed using the SPSS version 22.0 program. Data analysis techniques used to test the hypothesis using the Classic Assumption Test formula, Multiple Linear Regression Analysis, Correlation Coefficient, Determination, Regression Coefficient Test together (f test) and Partial Regression Coefficient Test (t test).The results of data analysis obtained from 94 respondents, obtained values in the equation Y = 1.711 + 0.213X1 + 0.715X2 and adjusted R square (R2) of 0.843 or 84% of the variables X1 and X2. From the description above, it can be concluded that the Regional Financial Management Information System and Financial Technical Guidance influence and significantly affect the Quality of Local Government Financial Reports in Lebak Regency.